Correlation of Clinical Patterns of Oral Squamous Cell Carcinoma with Age, Site, Sex and Habits - Prerna Taneja Mathur; P K Dayal; Keerthilata M Pai (Wolters Kluwer Medknow Publications, 2011)
Oral cancer is one of the 10 most common cancers of world. The histological type referred to is squamous cell carcinoma. The present study is conducted to find out if there is any correlation between clinical patterns of squamous cell carcinoma (papillary, ulcerative and deeply infiltrative) with age, site, sex and habits. The present study derived a positive correltion of clinical patterns of squamous cell carcinoma with site, more studies should be done to validate this fact.